Evaluasi Penerapan Metode Acceptance Sampling Berdasarkan Standar MIL-STD-105E dalam Pemeriksaan Kualitas Bahan Baku Whey Powder - Edel Wahyu Yolanda Diaz; Dian Friana Hidayat; Agus Ruhimat; Diah Septiyana (Journal Industrial Manufacturing, 2026)
Raw material quality inspection plays an important role in maintaining the consistency of product quality in the food manufacturing industry. This study evaluates the implementation of the existing acceptance sampling method used for whey powder inspection at an FMCG company and compares it with a proposed method based on the MIL-STD-105E standard. The research employed an observational approach using primary and secondary data, including incoming material records, lot sizes, sample sizes, and production reject data. The study was conducted in two stages: evaluation of the company's existing inspection method using inspection data from November 2025 and a pilot implementation of the proposed MIL-STD-105E sampling plan during May–June 2026. Data analysis included descriptive analysis, probability of acceptance (Pa), Operating Characteristic (OC) Curve evaluation, and Average Total Inspection (ATI). The results indicate that the existing sampling method has not optimally represented the actual quality of incoming raw materials, as evidenced by several production rejects despite accepted inspection lots. The proposed MIL-STD-105E sampling plan improved inspection effectiveness by determining more appropriate sample sizes and acceptance criteria. During the pilot implementation, observed production rejects decreased from 171 sacks to 5 sacks, demonstrating improved capability in identifying non-conforming lots before entering the production process. Therefore, the proposed acceptance sampling method can be considered a more effective approach for supporting raw material acceptance decisions while maintaining inspection efficiency. Keywords: Acceptance Sampling, MIL-STD-105E, Operating Characteristic Curve, Quality Control, Whey Powder